A Model for Reduced HIV-1 Viral Load Monitoring in Resource-Limited Settings. (February 2013) - Bryant, LeeAnn; Smith, Nathaniel; Keiser, Philip
Background: Viral load monitoring of antiretroviral therapy in low-income countries is rarely used because of high costs. Reducing the frequency of monitoring may make it financially feasible. Methods: We modeled three testing schemes: reduced viral load monitoring (RVLM) with CD4 count at baseline and viral load testing at 6, 36, and 60 months; United States Department of Health and Human Services (US DHHS) Treatment Guidelines; and World Health Organization (WHO) Guidelines using a cohort of 313 HIV-infected patients using Kaplan-Meier analysis. Results: Median time to detection of antiretroviral therapy (ART) failure using RVLM was 147 days; using US DHHS, it was 115 days; and using WHO guidelines, it was 1110 days. Median time for the development of first thymidine analog mutation was 594 days. The cost of RVLM was significantly lower than US DHHS. Conclusions: RVLM detected failure significantly sooner than CD4 count monitoring alone at a lower cost than US DHHS monitoring. RVLM is a potentially effective method of monitoring ART in resource-limited settings.